(untitled) (Semiárida, 2020)
It is assumed that grasslands’s species growing naturally in the semiarid pampas of Argentina have good nutricional quality but there are not enough information about it. The purpose of this work was to gain from degradability a comprehensive knowledgment of the forage quality of key species and the potential quality of grasslands communities. The objective was to determinate the degradability of native species incubated separately in the rumen for 3, 6, 9, 12, 24, 48, 72 and 96 hours throughout the year. Their degradation characteristic were described by the exponential equation p= a+b(1-e-Ct ), were p Is the degradation at time t, a is the soluble fraction or wash value, b Is the degradable part of insoluble fraction and e is the fractional degradation rate. These results show that Poa ligularis have the higher (a+b) value (71.7-79.2%), then Piptochaetium napostaense with 50-68% and Sorghastrum pellitum with 49.6-68. Solubility was the parameter more dependent of phenological moments and less the the fractional degradatlon rateo The potentlal degradabllity was de most stable throughout the year. These results suggest that phytomass of Poa ligularis and Piptochaetium napostaense have a good nutritive value during the year; in contrast, Sorghastrum pellitum only in the growth period. The others species analysed here contribute to grassland with good nutritional value in differents moments, specially when winter species were the lowest growth in the summer.